Implementasi Pohon Literasi Pada Program Kampus Mengajar di SD 81 Bukamata - Ashar, Ashar; Idamayanti, Reski (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Kampus Mengajar Program aims to improve the quality of education in regional schools through student involvement in community service activities. This service discusses the implementation of the Literacy Tree as an innovation in building a culture of literacy at SD 81 Bukamata. The service aims to increase students' interest in reading at SD 81 Bukamata through a creative and innovative approach, develop a culture of literacy in the school environment, provide a fun and meaningful learning experience for students, encourage the involvement of teachers, parents, and the community in supporting literacy programs. The methods used include initial observation, making Literacy Tree media, implementing daily reading activities, and evaluating student development. The results showed a significant increase in student participation in literacy activities, strengthening the culture of reading in schools, and close collaboration between teachers, students, and parents. This program also succeeded in creating an interactive and fun learning atmosphere. With the Literacy Tree, students are not only encouraged to read but also to write and speak more confidently. This program is expected to be a model to be implemented in other schools in order to build a broader and more sustainable literacy ecosystem.